2003
DOI: 10.1111/j.1349-7006.2003.tb01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cell death induced by ethacrynic acid in a human colon cancer cell line DLD‐1 and suppression by N‐acetyl‐l‐cysteine

Abstract: Since ethacrynic acid (EA), an SH modifier as well as glutathione S-transferase (GST) inhibitor, has been suggested to induce apoptosis in some cell lines, its effects on a human colon cancer cell line DLD-1 were examined. EA enhanced cell proliferation at 20-40 µ µ µ µM, while it caused cell death at 60-100 µ µ µ µM. Caspase inhibitors did not block cell death and DNA ladder formation was not detected. Poly(ADP-ribose) polymerase, however, was cleaved into an 82-kDa fragment, different from an 85-kDa fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 42 publications
1
56
0
Order By: Relevance
“…Several studies have shown that the depletion of GSH by EA results in an oxidant stress that causes cell death (21,22). In addition, it has been suggested that activation of the MAPK pathway may also participate in the cell death process induced by EA (19). The structure of EA has been modified, and we found that EA esters retained GSTP1-1 inhibition ability and also had an increased ability to inhibit leukemia cell growth (23).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Several studies have shown that the depletion of GSH by EA results in an oxidant stress that causes cell death (21,22). In addition, it has been suggested that activation of the MAPK pathway may also participate in the cell death process induced by EA (19). The structure of EA has been modified, and we found that EA esters retained GSTP1-1 inhibition ability and also had an increased ability to inhibit leukemia cell growth (23).…”
Section: Introductionmentioning
confidence: 82%
“…EA inhibits cell growth and induces apoptosis in tumor cells at high concentrations by an unknown mechanism (19,20). Several studies have shown that the depletion of GSH by EA results in an oxidant stress that causes cell death (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Ethacrynic acid at high concentrations induces cell death and apoptosis (10,37) and several groups, including ours, found that the cytotoxic effect of ethacrynic acid requires the a,b-unsaturated carbonyl group (7,9,38). Disruption of the a,b-unsaturated carbonyl group abrogates the cytotoxic effect of ethacrynic acid (7).…”
Section: Discussionmentioning
confidence: 99%
“…Although ethacrynic acid is considered a GSTP1-1 inhibitor, ethacrynic acid alone has been reported to be cytotoxic in many malignant cells (9,10). By conducting structural activity analyses, it was found that the a-, b-unsaturated carbonyl structure is required for its ability to inhibit leukemia cell growth (7,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation